2022
DOI: 10.9745/ghsp-d-21-00689
|View full text |Cite
|
Sign up to set email alerts
|

Drivers and Barriers to Improved Data Quality and Data-Use Practices: An Interpretative Qualitative Study in Addis Ababa, Ethiopia

Abstract: The Ethiopia government’s implementation of strategies to improve data quality, as outlined in its Information Revolution Roadmap, has led to higher data quality and improved data use, but barriers to optimal data-use practices must be addressed to create a culture of information use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Studies have also shown good consistency of reporting on deliveries and livebirths comparing HMIS data and source documents, as was observed in the government facilities veri ed in this study (9,43). The observed data quality problems may also be attributed to factors such as high work load, lack of reporting tools, lack of training and supportive supervision that have been reported eleswhere (21,22,24,25,44).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Studies have also shown good consistency of reporting on deliveries and livebirths comparing HMIS data and source documents, as was observed in the government facilities veri ed in this study (9,43). The observed data quality problems may also be attributed to factors such as high work load, lack of reporting tools, lack of training and supportive supervision that have been reported eleswhere (21,22,24,25,44).…”
Section: Discussionsupporting
confidence: 70%
“…From the ndings of this study, we recommend tailored support to be provided to private-for-pro t and lower-level (non-EmOC) facilities to report correctly and consistently the services provided and health outcomes. This could be done by linking routine data reviews with on-job mentoring in the different facilities and capacity building among other strategies (31,44). Also, given that majority of facilities were at lower-levels of the system and therefore submit their reports to the district o ces, strengthening the data transmission processes may also help to improve completeness of data.…”
Section: Recommendationsmentioning
confidence: 99%
“…The study also explored the poor skill and commitment from the leadership as potential barriers to initiating and implementing the HIS accountability framework, which aligns with different research in different parts of the country (23)(24)(25). So, it is recommended that they work on enhancing their skills and commitment by using different modalities like capacity-building, training, and experience-sharing(26).…”
Section: Discussionmentioning
confidence: 99%
“…Together, the articles yield a rich picture of the factors that underpinned early program achievements and how evidence informs strategy to improve data-use practices during the later stages of the program. 33 Worku et al explored whether there were preproject associations between the strength of routine health information systems and maternal health care seeking. 34 The findings suggest patterns and frame hypotheses that Ethiopia Data Use Partnership researchers will explore at later stages of their program.…”
Section: Helping Primary Health Care Systems Bridge the Know-do Gapmentioning
confidence: 99%